2010
DOI: 10.1634/theoncologist.2010-0095
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Pazopanib in Combination with Weekly Paclitaxel in Patients with Advanced Solid Tumors

Abstract: Purpose. To evaluate the maximum tolerated regimen (MTR), dose-limiting toxicities, and pharmacokinetics of pazopanib, an oral small-molecule tyrosine kinase inhibitor of vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and c-Kit, in combination with paclitaxel.Patients and Methods. Pazopanib was given daily with weekly paclitaxel on days 1, 8, and 15 every 28 days. Dose levels of pazopanib (mg/day)/paclitaxel (mg/m 2 ) were 400/15, 800/15, 800/50, and 800/80. An expanded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
4
32
1
Order By: Relevance
“…A drug-drug interaction was expected, because paclitaxel is a substrate for CYP2C8 and CYP3A4, and pazopanib is a weak inhibitor of CYP3A4 and CYP2C8. The extent of the interaction observed in this study appears similar to that previously reported for pazopanib in combination with paclitaxel administered on a weekly schedule (25), and in combination with paclitaxel and carboplatin (23) administered with various doses of pazopanib. Collectively, these studies suggest that coadministration of pazopanib results in a consistent increase in systemic exposure to paclitaxel regardless of the paclitaxel dose regimen and pazopanib doses investigated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A drug-drug interaction was expected, because paclitaxel is a substrate for CYP2C8 and CYP3A4, and pazopanib is a weak inhibitor of CYP3A4 and CYP2C8. The extent of the interaction observed in this study appears similar to that previously reported for pazopanib in combination with paclitaxel administered on a weekly schedule (25), and in combination with paclitaxel and carboplatin (23) administered with various doses of pazopanib. Collectively, these studies suggest that coadministration of pazopanib results in a consistent increase in systemic exposure to paclitaxel regardless of the paclitaxel dose regimen and pazopanib doses investigated.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies demonstrated that pazopanib could not be readily combined with paclitaxel 175 mg/m 2 and carboplatin area under the plasma drug concentration curve (AUC) 5 administered every 3 weeks at doses higher than pazopanib 200 mg (23,24). However, it was feasible to administer pazopanib 800 mg with a weekly regimen of paclitaxel 80 mg/m 2 , which resulted in a 26% higher geometric mean paclitaxel AUC that was similar to the systemic exposure of a paclitaxel dose of 100 mg/m 2 (25). This study was designed to evaluate the safety of pazopanib in combination with paclitaxel administered every 3 weeks, and to determine the recommended phase II dose for this combination in the first-line setting in patients with advanced solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of pazopanib 200 mg (n ¼ 14) and 400 mg (n ¼ 8) once daily with paclitaxel 175 mg/m 2 and carboplatin every 21 days decreased paclitaxel clearance by 30% and 17%, respectively, and increased paclitaxel C max by approximately 40%. Mean paclitaxel clearance decreased by 14% and mean paclitaxel C max increased by 36% after administration of pazopanib 800 mg once daily and paclitaxel 80 mg/m 2 in a weekly regimen (18). These results indicate that maximal inhibition of paclitaxel clearance is achieved at pazopanib doses at or below 200 mg.…”
Section: Discussionmentioning
confidence: 70%
“…A phase I trial had previously shown that administration of pazopanib at 800 mg once daily reduced paclitaxel clearance by approximately 14% (18). Therefore, paclitaxel 175 mg/m 2 and carboplatin AUC6 administered intravenously every 21 days and pazopanib 800 mg once daily were chosen as the starting doses to achieve a predicted systemic exposure to paclitaxel similar to that following administration of paclitaxel 200 mg/m 2 and carboplatin in the absence of pazopanib.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, the drug-drug interaction may not always be clinically relevant (eg, minimal pharmacokinetic changes from clindamycin-paclitaxel combination and minimally increased plasma paclitaxel when given in combination with pazopanib). 52,53 In patients with hepatic dysfunction, the same dose modification scheme recommended for sb-paclitaxel is safe and feasible for nab-paclitaxel. 54 …”
Section: Gupta Et Almentioning
confidence: 99%